News Content Analysis of Sustainable Development Goals (SDGSs) Coverage at PT Astra International Tbk from a Media Relations Perspective - Jihan Aqilah Febianty; Azmawati, Azwan Asman; Anna Agustina; Sudarto (Faculty of Communication Science | Universitas Pancasila Jakarta, Indonesia, 2023)
This study was conducted on the basis that a company's media relations ideally maintain good communication with the media. The SDGs that the company does are important things that the company needs to convey to the media. The purpose of this study is to identify what SDGs messages are covered by media in Indonesia. Indonesia became one of the countries that contributed and committed to the implementation of the SDGs program, which included private parties that became the focus of research through the SDGs coverage conducted by PT Astra International Tbk which always involved the role of the media. The concepts used in this study were those proposed by Cangara, namely communication strategies with 3 main dimensions, planning, implementation and evaluation and completeness of news content with 5W1H main dimensions. This study used a qualitative approach with content analysis methods. The results of this study suggest that the media tends to be incompletely reporting activities about SDGs. Only 28% of news corresponds to the concept of communication strategy and only 27% of news corresponds to the concept of completeness of news content. For the media involved in the coverage of SDGs activities carried out by PT Astra International Tbk, it must be complete in news writing consisting of planning, implementation, evaluation, and complete with 5W1H. If incomplete, it is feared that it can have an impact on the appearance of public perceptions that are not intact in understanding SDGs' activities. Media relations companies should be careful in choosing media with high credibility. Comprehensive media is one of the most credible media for the company. This study has the limitation of using only a qualitative approach, it is hoped that subsequent studies will use a quantitative approach with regard to the elements present in this study.